Carbon recovery and re-utilization (CRR) from the exhaust of a solid oxide fuel cell (SOFC): Analysis through a proof-of-concept. (March 2017) - Santarelli, M.; Briesemeister, L.; Gandiglio, M.; Herrmann, S.; Kuczynski, P.; Kupecki, J.; Lanzini, A.; Llovell, F.; Papurello, D.; Spliethoff, H.; Swiatkowski, B.; Torres-Sanglas, J.; et al.
Highlights: The first SOFC-based poly-generation system with complete CO2 recovery is presented. The oxy-combustion and H2 O separation steps do not present technical limitations. The photobioreactor has revealed as the most problematic component of the chain. Micro-algae are really a fast growing biomass (weekly peak of 4.18 W/m 2 ). The CO2 emissions from the system are 0 kgCO2 /kWhel if a CO2 buffer is considered. Abstract: In the context of the paradigm of Carbon Recovery and Re-utilization (or CRR), this work investigates the role of electrochemical generators (such as high-temperature fuel cells) to perform CRR as a practical secondary effect. In fact, the solid oxide fuel cell (SOFC) operating principle is inherently beneficial toward CO2 separation from the exhaust gas since the fuel is electrochemically oxidized resulting in no N2 mixing at the anode (fuel) electrode. An oxy-combustor downstream the fuel cell will complete the residual fuel (mostly H2 and CO) oxidation to yield a stream that contains only H2 O and CO2 . After water condensation and further drying, the captured CO2 is fed to a photobioreactor that can fix carbon into microalgae. In this work, results of the first SOFC-based poly-generation system with complete CO2 recovery in the form of fast-growing biomass (micro-algae) are presented, as developed in the EU-funded project SOFCOM (GA 278798, www.sofcom.eu ). The overall plant layout is described, and results on the performance of the proof-of-concept plant units are provided.